1999
DOI: 10.1128/iai.67.3.1056-1062.1999
|View full text |Cite
|
Sign up to set email alerts
|

Role ofBordetella pertussisVirulence Factors in Adherence to Epithelial Cell Lines Derived from the Human Respiratory Tract

Abstract: During colonization of the respiratory tract by Bordetella pertussis, virulence factors contribute to adherence of the bacterium to the respiratory tract epithelium. In the present study, we examined the roles of the virulence factors filamentous hemagglutinin (FHA), fimbriae, pertactin (Prn), and pertussis toxin (PT) in the adherence of B. pertussis to cells of the human bronchial epithelial cell line NCI-H292 and of the laryngeal epithelial cell line HEp-2. Using B. pertussis mutant strains and purified FHA,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
0
2

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(26 citation statements)
references
References 54 publications
0
24
0
2
Order By: Relevance
“…B. pertussis colonises the respiratory tract and is thought to preferentially adhere to ciliated epithelial cells [18] and also possibly to alveolar macrophages [11,19,20]. BapC and BrkA reveal presence of integrin binding RGD motifs as well as glycosaminoglycan-binding motif SGXG (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…B. pertussis colonises the respiratory tract and is thought to preferentially adhere to ciliated epithelial cells [18] and also possibly to alveolar macrophages [11,19,20]. BapC and BrkA reveal presence of integrin binding RGD motifs as well as glycosaminoglycan-binding motif SGXG (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…To date, antigenic divergence between vaccine strains and clinical isolates has been observed with regard to two virulence factors: pertactin (Prn) and pertussis toxin (PT); and it has been suggested that these changes may have contributed to current pertussis epidemics [4]. Recently we described a role for the bacterial virulence factor ®lamentous haemagglutinin (FHA) as a major factor in colonization of the entire respiratory tract [5]. The existence of antigenic variation in this molecule, however, awaits to be con®rmed.…”
Section: Introductionmentioning
confidence: 99%
“…PRN belongs to the type V autotransporter protein family and, similar to FHA, contains an RGD domain as well (18). Several in vitro studies have demonstrated PRN to function as an adhesin (19,32,36,71); however, an exact host receptor has not been identified. The role of PRN as a protective immunogen is more clearly defined.…”
mentioning
confidence: 99%